RESPON BEBERAPA TAKARAN KOMPOS TANDAN KOSONG KELAPA SAWIT (ELAEIS GUINEENSIS JACK) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI GOGO (ORYZA SATIVA L) - Yusnaweti, Yusnaweti (Ensiklopedia of Journal, 2024)
Research in the form of field experiments ith the title “The Response Of Several Doses Of Oil Palm Empty Fruit Bunch Compost On The Growth And Yield Of Upland Rice Plants” hass been implemented on the campus of the fakulty of Agriculture, University of Muhammadiyah, West Sumatera, Tanjung Gadang Koto Nan Ampek  est Payakumbuh districts, ith inceptisol soil type. Altitude ± 514 mdpl. The time of the research as carried out for 3 months, namely from February to May 2020. The experiment used a randomized block design (RAK), where there are 5 treatments and 4 groups so that the total consists of 20 experimental plots. Each plot has 20 clumps with 3 as sample plants . As for the treatment given is the provision of several doses of empty palm fruit bunch compost as follows: A. 0 ton/ha, B. 5 ton/ha, C. 10 ton/ha, D. 15 ton/ha, E. 20 ton/ha. Observational data were averaged and statistically with the F tst at the level of 5% if F count is large from F table 5% then continued with Duncan’s F test new multiple range test (DNMRT)  at 5% level. The observations made were plant height (cm), number of tillers and number of productive tillers, longest panicle length (cm), longest number of seeds per panicle (cm),weight of 100 seeds (g), weight of grain per clump (g), weight of grain per plot (g), weight of grain per hectare (g). From the exsperimental results, it can be concluned that the application of 5 ton/ha of empty palm oil bunches compost showed the best growth and yields for upland rice plants. Keywords: Compost Oil palm empty bunches, Growth and Yield, Upland Rice.